Agile Leadership - Consideration of The Success Factors In the Corporate Environment - Jens BERGER (Communications of International Proceedings, 2023)
Agile leadership is a corporate response to the accelerated changes brought about by globalisation and digitalisation. The focus is on reacting flexibly and quickly to trends and changes and finding innovative solutions. Agility refers to the organisational structure and the mentality of the employees. This enables them to counteract demographic change and the increasing shortage of skilled workers. Agile leadership uses flat hierarchies, individual staff development and a people-oriented management style. Numerous companies in Germany already have experience with this. Agile methods are used in various sectors. Especially in IT. The use in other sectors is significantly lower. This study serves as a decision-making aid for organisations that want to familiarise themselves with the advantages and challenges of agile working methods. It highlights research findings and brings them together with a view to recommended leadership behaviour. New explanatory approaches are formed. Agility as leadership of the future is flexible and open to new impulses. Indispensable in dynamic markets of the future. Trust in employees promotes motivation. Decisions are made as a team. Open communication and continuous, constructive exchange in the team are important. Leaders define motives and the purpose of their actions. Leadership in the future will be based on trust and not on power. Responsible leaders strengthen the self-efficacy of their employees. The ability to develop a powerful culture is crucial for the success of an organisation. Employees should be involved, their skills used, and a positive culture of error created.
Keywords: Agile Leadership; self-functionality; self-efficacy; future leadership